From Folk Taxonomy to Species Confirmation of Acorus (Acoraceae): Evidences Based on Phylogenetic and Metabolomic Analyses - Cheng, Zhuo; Shu, Hang; Zhang, Shuang; Luo, Binsheng; Gu, Ronghui; Zhang, Ruifei; Ji, Yuanyuan; Li, Feifei; Long, Chunlin (Frontiers in Plant Science, 2020)
Plants in Acorus have been used as herbal medicine by various linguistic groups for thousands of years. Arguments of taxonomy of Acorus among scientists resulted in confusions and misuses of Acorus plants. The present study used different methods to investigate the classification of the genus, based on folk taxonomy. The relationships among Acorus species were revealed through phylogenetic analyses by constructing the Maximum Likelihood and Bayesian phylogenetic analyses based on sequences of two chloroplast regions (trnL-trnF and rbcL). All samples named with two so-called synonyms, Acorus macrospadiceus (Yamam.) F. N. Wei & Y. K. Li and Acorus tatarinowii Schott collected from different habitats, were clustered into separate groups, which revealed that they represented two independent species. Multivariate statistical analysis of metabolites from different Acorus populations were carried out based on UPLC-QTOF-MS data. Three independent analysis, principal component analysis, heat-map analysis, and hierarchical cluster analysis, showed that A. macrospadiceus and A. tatarinowii are different from two recognized species in the genus, A. calamus L. and A. gramineus Aiton. The results of phylogenetics and chemotaxonomy, together with morphological and ecological evidences, were consistent with traditional knowledge of local people related to Acorus taxa, which proved the significance of parataxonomy. Multiple evidences including morphological, ecological, folk taxonomic, phylogenetic and chemical taxonomic results suggested that there are four species in the genus Acorus.